Risk-Taking Behavior and Capital Adequacy in a Mixed Banking System: New Evidence from Malaysia Using Dynamic OLS and Two-Step Dynamic System GMM Estimators - Wahab, HA; Saiti, B; Rosly, SA; Masih, AMM (Routledge Journals, Taylor & Francis Ltd, 2024)
This study is the first attempt to investigate the relationship between the level of risky assets and capital level in a mixed Malaysian banking system covering 83months starting December 2006. The results of dynamic ordinary least squares indicate positive relationship between capital ratio (CAR) and risk-weighted asset ratio (RWA) in the long run. Furthermore, the causality analysis based on panel vector error correction model (VECM) and two-step dynamic system generalized method of moments indicates unidirectional causality from CAR to RWA. Our results further suggest that higher capital growth and capital buffer provide an extra cushion for the Malaysian banks to pursue relatively riskier financial activities, and the nature of risk-taking behavior of Islamic banks follows that of the conventional banks.